ESRA19-0449 Adductor canal block versus femoral nerve block in total knee arthroplasty: a meta-analysis of randomized control trials. (30th August 2019) - Maye, A; Hurley, E; Jamal, M; Curley, G
Abstract : Background and aims: Total knee arthroplasty is a commonly performed orthopaedic procedure and is associated with significant postoperative pain. Increasingly in recent years the trend has been towards advocating earlier mobilization of patients postoperatively to facilitate recovery and prevent complications. The aim of this study was to assess if adductor canal block (ACB) could provide similar analgesia to femoral nerve block (FNB) while sparing motor function of the quadriceps muscles. Our hypothesis was that ACB would result in equivocal analgesia with earlier mobilization and shorter length of stay. Methods: A literature search was carried out according to the PRISMA guidelines. The studies were stratified into continuous versus single shot. The outcomes measured were pain, opioid consumption, patient satisfaction and length of stay (LOS). A p-value of <0.05 was considered statistically significant. Results: 12 RCTs were identified with 969 patients. At 24 hours at rest there was a significant different in pain score in favor of continuous ACB (p<0.00001) and at 48 hours at rest there was a significant difference in pain scores in favor of single-shot FNB (p<0.0001). Patient satisfaction was significantly higher in ACB, both in the continuous subgroup and overall (p = 0.04, p = 0.02 respectively). There was a significant difference in LOS in favor of ACB (p<0.00001). Conclusions: ACB, whether single-shot or continuous, resulted in similar levels of analgesia to FNB while preserving quadriceps strength in the early postoperative course and leading to shorter LOS and increased patient satisfaction.